The Study of Economic Feasbility Project of Embung’s Establishment in The Case to Supply People Needs of Water Sources (Study Case Project of Embungkalimati, Bapangan-Jepara District) - Slamet Imam Wahyudi; Faiqun Ni’am; Ahmad Hidayawan (International Conference on Coastal and Delta Areas, 2017)
Embungkalimati was a water building which utilize the stream water remains. Embung is located in Bapangan village, Jepara district. Embung establishment is functionate to supply people needs of water sources. Embungkalimati has 280 m of length with depth excavation upstream between 4,80 m and downstream about 2,60 m with wide of pool storage 22.950 m2. Embungkalimati could save 115.890 m3 of water volume. The capacity of water storage is 107.000m3. this study is purpose to calculate the costs of embung’s establishment, to find out the benefits and analixing the economic feasibility. Economic feasibility is calculated by comparing the benefits and the costs of benefits and costs rasio (B/C). The result of this study found that the costs of establishment is Rp 21.964.132.000,00. The calculate of the costs based on the price tag of water is B/C>1, it can be obtained the costs water Rp2.280/m3 for B/C 1,07, IRR 11%, the sensitivity is increase up to 10% and the benefits decrease up to 10% which is can be said that it was impact to the value of the costs and benefits. The Payback Period is still the same with the 8th year. So, it can be concluded that the project of Embungkalimati’s establishment project was appropriate for economics. Keywords: Costs of establishment, Price tag of water, B/C, IRR